(untitled) (Fiep Bulletin - online, 2014)
This descriptive study had as objective to investigate 12 to 14 year school students´ competence perception from the city of Cascavel - Paraná. The aim was to verify the competence perception profile and to compare the levels of competence perception between genders, different schools and the students who participated the sports training with those who didn’t. The sample was constituted of 41 students. Perceived Competence Scale for Children from Harter (1985) adapted by Fiorese (1993) was used as measure instrument. The data were evaluated by descriptive statistics analyses and the t of Student test. The results showed that exists significant difference (P<0,05) for the cognitive, global value and motor subscales, for the values distributed by gender, by school and by participants of the sports training, respectively. However, the children evaluated in this study apparently feel good about them selves, showing that they perceive that are living according to their objective and values.